The Original Language of the Lukan Infancy Narrative. By Chang-Wook Jung - Williams, P. J. (The journal of theological studies, 2007)
This is the published version of a Ph.D. dissertation written under Prof. M. C. de Boer at the Free University in Amsterdam. It contains three core chapters and a conclusion. The first surveys the history of scholarship on the language of Luke's Gospel as a whole and especially of its first two chapters. The second seeks to establish clarity in discussion by providing rigorous definitions of terms such as ‘Semitism’, ‘Septuagintalism’, ‘Lukanism’, and ‘Non-Lukanism’—the last one being a feature not found in Luke 3–24 or Acts. Jung also introduces a distinction between ‘hard core Septuagintalisms’ and ‘secondary Septuagintalisms’.